Head and neck cancer in South Asia: macroeconomic consequences and the role of surgery. (27th April 2015) - Alkire, Blake C; Bergmark, Regan W; Chambers, Kyle; Cheney, Mack L; Meara, John G
Abstract: Background: Head and neck cancer, for which the diagnosis and treatment are often surgical, comprises a substantial proportion of the burden of disease in South Asia. Further, estimates of surgical volume suggest this region faces a critical shortage of surgical capacity. We aimed to estimate the total economic welfare losses due to the morbidity and mortality of head and neck cancer in India, Pakistan, and Bangladesh for 1 year (2010). Methods: We used publicly available estimates from the Institute for Health Metrics and Evaluation regarding the morbidity and mortality of head and neck cancer in India, Pakistan, and Bangladesh, along with an economic concept termed the value of a statistical life, to estimate total economic welfare losses due to head and neck cancer in the aforementioned countries in the year 2010. The counterfactual scenario is absence of disease. Sensitivity analyses were done with regard to how the value of a statistical life changes with income. Findings: In 2010, the most conservative estimate of economic welfare losses due to head and neck cancer in the three studied countries is US$16·9 billion (2010 USD, PPP), equivalent to 0·26% of their combined gross domestic product (GDP). The welfare losses experienced by the population younger than 70 years of age accounted for US$15·2 billion (90% of the total losses). When adjusted for the size of their respective economies, Bangladesh, the poorest of the three countries, incurred the greatest loss (US$930 million), equivalent to 0·29% of its GDP. India and Pakistan experienced welfare losses of US$14·1 billion and US$1·9 billion, respectively. These figures are equivalent to 0·26% of the GDP for both countries. Oropharyngeal and hypopharyngeal cancer made up the largest share of the total burden at 39% (US$6·6 billion), followed closely by oral cavity cancer at 34% (US$5·7 billion). Interpretation: The burden of non-communicable diseases, to which cancer contributes greatly, is growing at a rapid pace in South Asia. Head and neck cancer is a leading cause of cancer-related mortality in this region, and this study suggests that the associated economic welfare losses, estimated to be US$16·9 billion in 2010 alone, are substantial. A number of strategies are available to address this burden. Surgery, as part of a multidisciplinary approach that includes radiation therapy and chemotherapy, plays a central part in the diagnosis and treatment of head and neck cancer, and building surgical capacity, which offers large economies of scope and scale, can not only address the burden of head and neck cancer, but also create a platform for beginning to confront the rising tide of non-communicable diseases. Funding: None.